2018
DOI: 10.17816/maj18272-77
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Neutrophil Extracellular Traps in Type 2 Diabetes Mellitus Patients With Suppurative and Necrotic Complications

Abstract: Aim of the study. Neutrophil extracellular traps (NETs) have been reported to participate in many pathological processes, which points at NET concentration in blood as an important indicator of the body condition. When studying NETs, their blood concentration is usually evaluated indirectly, which has a number of shortcomings. We aimed to measure directly the amount of NETs as integral structures, using blood smears as a most suitable tool for clinical practice, and to carry out measurements of NET levels in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…T2DM complicated by purulent necrotizing ulcers on the lower limbs is characterized by a long progressive course, which is associated with the development of vascular pathology and chronic nonhealing wounds with chronic inflammation. We have previously shown that the blood of mostly severe patients has high concentrations of NETs [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T2DM complicated by purulent necrotizing ulcers on the lower limbs is characterized by a long progressive course, which is associated with the development of vascular pathology and chronic nonhealing wounds with chronic inflammation. We have previously shown that the blood of mostly severe patients has high concentrations of NETs [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been indeed repeatedly observed that excessive NET formation is linked to the development of autoimmune, cardiovascular, and endocrine diseases, including diabetes mellitus. In particular, our data have shown that in type 2 diabetes mellitus (T2DM) patients with purulent necrotizing lesions of the lower extremities, a more severe clinical course is associated with a higher blood NET level [12,13]. NETosis promotes microthrombosis as well as causes delayed wound healing [9,14,15], which could have a negative effect on the healing process in T2DM patients.…”
Section: Introductionmentioning
confidence: 96%